Scientific Rationale and Clinical Basis for Clindamycin Use in the Treatment of Dermatologic Disease - Maria K. Armillei; Ivan B. Lomakin; James Q. Del Rosso; Ayman Grada; Christopher G. Bunick (MDPI AG, 2024)
Clindamycin is a highly effective antibiotic of the lincosamide class. It has been widely used for decades to treat a range of skin and soft tissue infections in dermatology and medicine. Clindamycin is commonly prescribed for acne vulgaris, with current practice standards utilizing fixed-combination topicals containing clindamycin that prevent Cutibacterium acnes growth and reduce inflammation associated with acne lesion formation. Certain clinical presentations of folliculitis, rosacea, staphylococcal infections, and hidradenitis suppurativa are also responsive to clindamycin, demonstrating its suitability and versatility as a treatment option. This review describes the use of clindamycin in dermatological practice, the mechanism of protein synthesis inhibition by clindamycin at the level of the bacterial ribosome, and clindamycin's anti-inflammatory properties with a focus on its ability to ameliorate inflammation in acne. A comparison of the dermatologic indications for similarly utilized antibiotics, like the tetracycline class antibiotics, is also presented. Finally, this review addresses both the trends and mechanisms for clindamycin and antibiotic resistance, as well as the current clinical evidence in support of the continued, targeted use of clindamycin in dermatology.